THE EFFECT OF RESTAURANT AND COFFE SHOP TAX INCOME ON INCREASING REGIONAL ORIGIN INCOME (PAD) ACCORDING TO ISLAMIC PERSPECTIVE (Study in Bandar Lampung City, 2016-2020) - Rahmalia Rahmalia; Alif Ilham Akbar Fatriansyah; Andueriganta Fadhlihi; Uus Diansyah (Jurnal Ilmu Ekonomi, 2023)
Restaurant Tax is a tax imposed on restaurant businesses, while coffee shop tax is a tax imposed on coffee shop services. Restaurant and coffee shop taxes are a component of local taxes which are a source of local revenue (PAD). The regional tax that is collected is Regional Original Revenue which is then used for the benefit of the common people. The method used in this study is a type of descriptive method with a quantitative approach. The type of data in this study is primary time series data sourced from BPPRD (2016-2020). This study uses Multiple Linear Regression Analysis supported by the SPSS version 26 program. Based on the results of data analysis, it can be concluded that Restaurant and Coffee Shop Taxes have a partial and simultaneous effect on increasing the Local Revenue of the city of Bandar Lampung. The Islamic Economic View of Taxes is permissible and justified, because taxes are a source of income that will be used for state management including the management of the development of the City of Bandar Lampung. Tax collection is permissible as long as it is in accordance with Islamic provisions or that has nothing to do with gambling or elements of maisir.